Impatiens glauca Hook. f. et Thomson—A little known Himalayan species with augmented description and a new spurless variety - Singh, Harsh; Sharma, Ashutosh; Adamowski, Wojciech (Phytotaxa, 2022)
Augmented description of Impatiens glauca based on observations of living material is given, as well as description of a new spurless variety. Global distribution, ecology, photographs and conservation status are also provided in detail. Abortive inflorescences are illustrated for first time.